The reflective futures practitioner: Balancing salience, credibility and legitimacy in generating foresight knowledge with stakeholders. (February 2015) - Kunseler, Eva-Maria; Tuinstra, Willemijn; Vasileiadou, Eleftheria; Petersen, Arthur C.
Highlights: We explore how foresight researchers balance legitimacy, credibility and salience. Generally, stakeholder participation is seen to benefit the quality of foresight knowledge. We found that stakeholder participation can jeopardise the balance as well. This happens when foresight researchers fail to respond to dynamics in the research setting. Therefore, we promote the need for 'reflective futures practitioners'. Abstract: This paper explores how foresight researchers involved in environmental, nature and planning issues attempt to balance salience, credibility and legitimacy while generating knowledge in interaction with policy-makers and other social actors. Engaging stakeholders in foresight processes can increase the robustness of foresight knowledge, broaden the spectrum of issues addressed, and create 'ownership' of the process. While in foresight practices stakeholder participation becomes more and more popular to resort to as enabling factor for generating salient, legitimate and credible foresight knowledge, participation can also compromise these qualities. We analysed two foresight projects conducted at the PBL Netherlands Environmental Assessment Agency, one that developed future visions for Dutch nature policy and another that focused on future pathways for Dutch urban sustainable development policy. We illustrate that the dynamics of the research setting – changes in the socio-political context and the internal dynamics of the participatory efforts – complicated the balancing process. We conclude that one of the main challenges for futures practitioners is, therefore, to work within the dynamics of the research setting, and to position themselves strategically in this setting; by acting as 'reflective futures practitioners'.